2020
DOI: 10.2147/copd.s243905
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum β2-Microglobulin is Associated with Mortality in Hospitalized Patients with Exacerbated Chronic Obstructive Pulmonary Disease</p>

Abstract: Purpose: We hypothesized that increased level of serum β2-microglobulin (β2M) is an independent factor associated with higher mortality in hospitalized patients with exacerbated chronic obstructive pulmonary disease (COPD). Patients and Methods: We retrospectively analyzed 488 hospitalized patients with exacerbated COPD as the first diagnosis at Beijing Chao-Yang hospital, P. R. China between December 31st, 2012 and December 28th, 2017. Concentrations of serum β2M and other clinical indexes were measured or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[48] Previous studies also reported the relationship between B2M and diseases related to immunity and inflammation. [10,49,50] B2M was also found to trigger an inflammatory process in vivo. [51] However, the influences of hypertension on mortality are unlikely to be dominated by the same pathways as for B2M.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Previous studies also reported the relationship between B2M and diseases related to immunity and inflammation. [10,49,50] B2M was also found to trigger an inflammatory process in vivo. [51] However, the influences of hypertension on mortality are unlikely to be dominated by the same pathways as for B2M.…”
Section: Discussionmentioning
confidence: 99%
“…The level of serum β2MG depends on the factors of production (non-kidney factors) and elimination (kidney factors). Due to these properties, β2MG is not only an ideal endogenous biomarker for estimating the glomerular ltration rate and AKI [6-9] and the adverse outcomes of chronic kidney disease [23], but also associated with a number of clinical states beyond kidney disease [11][12][13][14][15][16]. Several previous studies have shown that levels of serum β2MG are higher in patients with in ammatory bowel disease or systemic lupus erythematosus than in healthy controls, suggesting that it might also be a useful biomarker for the assessment of these autoimmune diseases [16,24].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of serum β2MG are independently associated with major cardiovascular events and mortality in the general population as well as in elderly patients and in patients with acute heart failure who do not have severe renal insu ciency [13,15,29]. Studies have shown that serum β2MG levels are also associated with poor outcomes in patients with COPD and in patients with acute pulmonary embolism [12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports about the relationship between β2M and peripheral organ diseases (including tumors) related to immunity and inflammation (Wilson et al, 2007;Josson et al, 2011;Hermansen et al, 2012;Mao et al, 2020), and the central nervous system (CNS) has traditionally been regarded as immune-privileged, though this has been questioned (Piehl and Lidman, 2001). The mechanism of β2M and poststroke immunity and inflammation may be complex, and there are relatively few reports.…”
Section: Introductionmentioning
confidence: 99%